: SOSIALISASI TENTANG PENERAPAN PROTOKOL KESEHATAN 5M SEBAGAI PENANGGULANGAN COVID-19 DI PUSKESMAS JAKABARING KABUPATEN BANYUASIN TAHUN 2021 - Dewi Sayati Sayati (IKesT Muhammadiyah Palembang, 2021)
The health center is at the forefront of breaking the chain of transmission of COVID-19. During this Covid-19 pandemic, Public Health Centers need to make various efforts to prevent and limit the transmission of infection. Breaking the Covid-19 chain is currently a priority for the health sector. A study on work motivation needs to be carried out because during the Covid-19 pandemic it takes work encouragement from health workers so that they can work optimally so that the role of puskesmas during the Covid-19 pandemic can be optimal. The high transmission power of this disease causes health workers, especially in health centers, to be vulnerable to this disease. The purpose of this activity is to increase the knowledge and understanding of the socialization participants about being able to know and apply the 5M health protocol as a response to covid-19. The method of implementing Community Service activities is in the form of socialization or counseling in interpersonal/individual communication to participants who visit the Jakabaring Health Center, Banyuasin Regency to obtain services, then a leaflet was given about the Implementation of the 5M Health Protocol as a Covid-19 Response at the Jakabaring Health Center, Banyuasin Regency. as many as 10 people. The results of the socialization activities for the participants showed that there was an increase in the knowledge and understanding of the participants regarding the material given with a total score in the percentage of 84%. The material presented can be understood by every participant of the socialization and is also very useful. which in turn can change the behavior of the community in the working area of ​​the Jakabaring Health Center, Banyuasin Regency in a positive direction, namely being able and always applying it in their daily life by carrying out the government's appeal regarding the Application of the 5M Health Protocol as a Covid-19 Countermeasure at the Jakabaring Health Center, Banyuasin Regency. The conclusion is that the knowledge and understanding of citizens about the procedures for preventing Covid-19 and the correct use of masks is increased. It is recommended to all participants who do not know and understand the implementation of the 5M Health Protocol as a Covid-19 Response at the Jakabaring Health Center, Banyuasin Regency.